Prevalence and root causes of operating room fires in the United States 2014–2024 - Monica M. Attia (Patient Safety in Surgery)
Abstract Background Operating room fires, though rare, pose serious risks to patient and operator safety. Among the known ignition sources, light-emitting surgical devices—including fiberoptic cables, headlamps, and light boxes—are increasingly recognized contributors. However, the true prevalence and underlying causes remain under-characterized in national surveillance data. This study hypothesized that operator error is a leading cause of light-source-related fires and sought to identify specific device types, procedural timing, and preventable risk factors involved in these adverse events. Methods Reports from the U.S. FDA’s MAUDE database were analyzed for light source-related operating room fires from January 1, 2014, to January 1, 2024. Events were categorized by device type, procedural timing, root cause, and resultant injury. Results A total of 45 adverse events were analyzed. Most fires were associated with light sources (33.3%), light headlamps (31.1%), and fiberoptic cables (20%). Intraoperative fires comprised the majority (35.6%). Operator error accounted for 37.8% of cases, with common errors including device mishandling (35.2%) and failure to detect damage (17.6%). Only 13.3% required intra-procedural interventions; injuries included one patient burn and two operator injuries. Conclusions Most operating room fires involving light sources were linked to modifiable operator errors. These findings underscore the urgent need for preventive strategies—including mandatory training, regular equipment checks, and improved design standards—to reduce intraoperative fire risk and enhance surgical safety.